Profiling Digital Competency of Prospective Vocational IT Educators Using Generalized DINA Model: A Cognitive Diagnostic Approach - I Nyoman Indhi Wiradika; Samsul Hadi; Mohammad Khairudin; Syarief Fajaruddin (Universitas Ahmad Dahlan, 2026)
Indonesia faces a significant shortage of digitally competent vocational teachers, yet existing assessment instruments often rely on aggregate scores that fail to diagnose specific cognitive deficits. This study addresses this gap by developing a diagnostic assessment instrument for vocational IT pre-service teachers. The research contribution is the validation of a domain-specific Cognitive Diagnostic Model (CDM) framework that integrates general digital pedagogy with vocational IT technical expertise, enabling precise attribute mastery profiling. The study employed a cross-sectional survey design with a purposive sample of 270 informatics education students. Data were analyzed using a multi-stage psychometric approach, combining Classical Test Theory (CTT), Confirmatory Factor Analysis (CFA), and the Generalized Deterministic Inputs, Noisy